1999
DOI: 10.1021/jm9806650
|View full text |Cite
|
Sign up to set email alerts
|

Lamellarin α 20-Sulfate, an Inhibitor of HIV-1 Integrase Active against HIV-1 Virus in Cell Culture

Abstract: HIV-1 integrase is an attractive target for anti-retroviral chemotherapy, but to date no clinically useful inhibitors have been developed. We have screened diverse marine natural products for compounds active against integrase in vitro and found a series of ascidian alkaloids, the lamellarins, that show selective inhibition. A new member of the family named lamellarin alpha 20-sulfate (1), the structure of which was determined from spectroscopic data, displayed the most favorable therapeutic index. The site of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
123
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 296 publications
(124 citation statements)
references
References 60 publications
1
123
0
Order By: Relevance
“…Similar to previous work that identified a number of sulfated marine natural products 15,68,102 and sulfated synthetic molecules 11,45,54 as IN inhibitors, we observed that three of the four sulfated molecules (16)(17)(18) were inhibitors. Specifically, they were more active than the parent hydroxyl compounds (1, 8, and 11).…”
Section: Resultssupporting
confidence: 89%
“…Similar to previous work that identified a number of sulfated marine natural products 15,68,102 and sulfated synthetic molecules 11,45,54 as IN inhibitors, we observed that three of the four sulfated molecules (16)(17)(18) were inhibitors. Specifically, they were more active than the parent hydroxyl compounds (1, 8, and 11).…”
Section: Resultssupporting
confidence: 89%
“…Recently, a number of compounds identified in cell-free assays have been shown to inhibit viral replication in cell culture without displaying significant cytotoxicity (15,26,31,39,44,45,49,50). AR177 (a G-quartet-containing oligonucleotide that forms highly stable intermolecular tetrad structures) and members of the bisaroyl hydrazine family of integrase inhibitors have been shown to inhibit in vitro integration reactions in the nanomolar and low micromolar ranges respectively (6, 37; N. Neamati et al, submitted for publication).…”
mentioning
confidence: 99%
“…in 1985 [42]. They were later extracted from various ascidians belonging to the Didemnum genus [43][44][45][46][47][48] and in some sponges [49,50] collected from widely varying locations, which suggests a potential microbial link to their biosynthesis.…”
Section: Bis-steroidal Pyrazines: Ritterazines and Cephalostatins Pomentioning
confidence: 99%